Restriction endonuclease analysis of the genomes of different isolates of chicken anemia virus amplified by polymerase chain reaction (SAARC Journal of Agriculture, 2018)
Four DNA fragments (fragments A, B, C and D) covering the whole genome of chicken anemia virus (CAV) were amplified enzymatically by polymerase chain reaction (PCR) using four pairs of oligonucleotide primers. The DNA fragments were amplified from each of nine CAV isolates including eight Malaysian isolates and one European isolate (Cux-1). For all nine CAV isolates, fragment A (1518 bp) was digested with one restriction enzyme, Eco130I (StyI); fragment B (926 bp) with three enzymes, Eco130I (StyI), HpaII and MboI separately; fragment C (675 bp) with also three enzymes, BsuRI (HaeIII), HinfI, and HpaII separately; and the fragment D (552 bp) with one enzyme, EcoRI. Enzyme digested products of different fragments were separated by agarose gel or polyacrylamide gel electrophoresis. Each of the eightenzymatic reactions differentiated at least two isolates except the HpaII digestion of fragment C where no isolate was distinguished. The overall restriction endonuclease (RE) analysis separated four isolates (BL-1, BL- 2, BL-4 and BL-5) in one group and the rest five isolates (SMSC-1, SMSC-2, 3-1, BL-3 and Cux-1) were differentiated from each other and also from the group of four isolates, based on the number of restriction site differences and the fragments generated by different enzymatic digestions. The study revealed that RE analysis could be used to identify and differentiate CAV isolates based on the number of restriction site differences. The study showed that more isolates, even the isolates from the same poultry farm, could be differentiated with proper genomic diversity after RE analysis of more genome fragments compared to that of single genome fragment.SAARC J. Agri., 15(2): 1-18 (2017)